THE LANGUAGE AND IDEOLOGY OF CAPITAL PUNISHMENT FOR DRUG CONVICTS FOUND IN SELECTED OPINIONS IN THE JAKARTA POST - Arina Isti’anah (Soegijapranata Catholic University, 2015)
This research is an investigation into the language use in peoples opinions of capital punishment for drug convicts in The Jakarta Post. Capital punishment was executed to six drug convicts on January 18th , 2015. Controversy about this action has risen before and after the execution. People give their opinions in social media, such as Facebook, Twitter, blogs, and newspapers. The Jakarta Post is a well-known English newspaper in Indonesia which has a lot of readers. People choose this newspaper to convey their ideas so that their opinions will be read by people around the world. As the issue about capital punishment is popular recently, this research attempts at finding out peoples ideology about capital punishment for drug convicts. Critical discourse analysis was conducted in this research as an approach to figure out how language use by the people can reveal their ideology of capital punishment. This research focused on observing four opinions of capital punishment for drug convicts in The Jakarta Post. The analysis shows that material processes dominate the opinions, followed by relational, mental and verbal processes. The ideologies revealed in the opinions are power, pessimism, and criticism. Before the execution, pessimism dominates the opinions, while after the execution criticism appears most in the opinions.